PPM PELATIHAN DOODLE SEBAGAI ART THERAPY TERHADAP KEMAMPUAN MOTORIK HALUS PADA KELOMPOK ANAK USIA DINI DI KECAMATAN BULAK - fifin dwi tyas; Aironi Zuroidah; Ressy Mardiyanti; Nita Nilam Sari; Angga Dani Prasetia (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2022)
The development of fine motor skills needs to be stimulated with the right strategy. Especially with this Pandemic condition, causing children to hold gadgets more often every day, this is what scares parents from excessive use of gadgets, which can cause some children's fine motor skills to still not fully develop well. This is proven when some children write letters, draw shapes and color they tend to not be able to reach the expected target, namely children still cannot write neatly, draw, color, and this low ability is not maximized because in moving the fingers they are still stiff. that is when holding a writing utensil is still not correct. These problems cause fine motor skills that need to be stimulated properly. The purpose of this service is to train fine motor skills for children in Bulak District, besides that it also makes children think creatively, innovatively and able to socialize with their friends. The method of implementation is through psychoeducation, art therapy training for early childhood children aged 4-5 years. The results of the service are expected that children are able to develop their fine motor skills optimally in a better direction, children can express themselves and be creative with various ideas and imaginations, and can grow the child's self-confidence. Keywords: Art Therapy, Fine Motor, Creative